Pest categorisation of Morganella longispina - EFSA Panel on Plant Health (PLH); Antonio Vicent Civera; Paula Baptista; Anna Berlin; Elisavet Chatzivassiliou; Jaime Cubero; Nik Cunniffe; Eduardo de laPeña; Nicolas Desneux; Francesco Di Serio; Anna Filipiak; Paolo Gonthier; et al. (EFSA Journal)
Abstract Following the commodity risk assessment of Acer palmatum plants grafted on Acer davidii from China, in which Morganella longispina (Hemiptera: Diaspididae) was identified as a pest of possible concern, the European Commission requested the EFSA Panel on Plant Health to conduct a pest categorisation of M. longispina for the territory of the European Union (EU). The origin of the scale insect M. longispina is uncertain, with either South America or eastern Asia suggested as the native range. The geographic distribution of the species includes many countries of the continents of Africa, North and South America, Asia and Oceania. M. longispina is polyphagous, feeding on plants assigned to 86 genera in 42 families. Important crops of the EU that may be affected by this insect are avocado, citrus, fig, peach, plum, olive and walnut. It is a viviparous insect with several generations per year in Algeria. Host availability and climate suitability indicate that the southern EU countries would support the establishment of M. longispina. The introduction of this pest would likely have an economic impact on several crops in the EU as it can cause significant damage to host plants. Uncertainty exists, however, about the magnitude of yield and quality losses due to the insect, and this is a key uncertainty. M. longispina is not listed in Annex II of Commission Implementing Regulation (EU) 2019/2072. Phytosanitary measures are available to reduce the likelihood of entry, establishment and spread of the pest into the EU. All criteria assessed by EFSA for consideration as a potential quarantine pest are met.